ANALYSIS OF NEED FOR DEVELOPMENT OF HOTS-BASED MATHEMATICS TEACHING MATERIAL IN ELEMENTARY SCHOOLS - Nurlaily, Vivi Astuti; Sholihah, Husna Imro’athush (PrimaryEdu : Journal of Primary Education, 2021)
One of the 2013 curriculum transformation elements in elementary schools is strengthening the learning process and familiarizing the development of higher-order thinking skills (HOTS) for students. This needs to be supported by teaching materials to support HOTS-based learning.This research aims to analyze the need for HOTS-based mathematics teaching materials in elementary schools. This research uses a descriptive approach. The subjects of this research were fourth-grade students of public elentary school in Tunjungan Blora area. The data collected in this research uses observation sheets, interviews, and document studies. Observations and interviews were carried out to teachers and fourth-grade students. Otherwise, the document studies were carried out on learning resources used in mathematics learning. The validity test data was conducted by using triangulation techniques. The results showed that: first, the characteristics of mathematics teaching materials used in elementary schools of Blora Regency have not described the HOTS material. Second, the need for teachers shows that the problems faced by teachers in learning mathematics have limited learning resources. Third, the student's need toward teaching material products is shown by the low interest of students in learning mathematics. Fourth, students have not been invited to think critically in learning mathematics.